Closing the gap: The need for military prosecution appeal right to ensure exclusive accessibility to justice - Haslida Isamail,; Mohamad Rizal Abd Rahman,; Muhamad Sayuti Hassan @ Yahya, (Penerbit Universiti Kebangsaan Malaysia, 2024)
With its unique characteristics and sui juris nature, the military justice system is designed specifically for the armed forces and operates independently from the civilian criminal justice system. The same applies in Malaysia, where the system also differs from the ordinary criminal justice system in several aspects, including the availability of appeals. While the Public Prosecutor and the accused in the civilian criminal justice system have the right to appeal against a court‘s decision, the right to appeal for the prosecution in a court-martial is absent. This study aims to examine the implication of the absence of the military prosecution appeal right in Malaysia, exploring its impact on fairness and effectiveness in relation to Sustainable Development Goal 16 (SDG Goal 16). The absence of the prosecution‘s right to appeal hinders their ability to seek justice in the military justice system and goes against SDG Goal 16, which promotes peaceful and inclusive societies for sustainable development, provides access to justice for all, and builds effective, accountable, and inclusive institutions at all levels. This study argues for the need to introduce a robust military prosecution appeal right in Malaysia‘s military justice system that would help promote peace, justice, and strong institutions. By addressing this gap, Malaysia can enhance the fairness and effectiveness of its military justice system, contributing to the broader objectives of sustainable development and justice for all.